Case report: Significant response to PD-L1 inhibitor after resistance to PD-1 inhibitor in an advanced alpha-fetoprotein-positive gastric cancer - Wang, Liyu; Feng, Ying; Huang, Anquan; Shi, Jianming; Zhang, Qinying; Zhu, Fan; Lv, Bin; Guo, Fen; Zou, Tianming; Zhang, Luyao (Frontiers in Oncology, 2022)
Alpha-fetoprotein-positive gastric cancer (AFPGC) is a type of gastric cancer with a high degree of malignancy. The disease is more common in the elderly, with a high prevalence in males and generally atypical clinical manifestations. For advanced patients, the current treatment options are limited and, to date, few cases of advanced AFPGC have been treated successfully with conventional chemotherapy. With the development of molecular biology and immunology, tumor immunotherapy offers more therapeutic options to patients with advanced gastric cancer. This study describes a case of advanced gastric cancer in a young woman with a high blood alpha-fetoprotein (AFP) level (>54,000 ng/mL). The patient showed initial promising results when programmed cell death-1 (PD-1) inhibitor treatment was combined with chemotherapy after systemic chemotherapy failed. When the disease progressed again after 129 days, adjustment of the treatment regimen to Atezolizumab in combination with Irinotecan and Surufatinib capsules achieved partial remission (PR). There were no immune-related pneumonia, myocarditis, or other adverse effects observed. The patient currently has an overall survival of more than 14 months. This case demonstrated that switching from PD-1 inhibitor to programmed cell death-Ligand 1 (PD-L1) inhibitor therapy may overcome potential resistance. It providing a reference for immunotherapy of patients with AFP-positive advanced gastric cancer.